Socio-Legal Construction of Marital Harmony in Polygamy: Comparing First–Second Wife Relations in Islamic and Sasak Perspectives - Daman Huri; Moh Yanto; Muhamad Ahyar; Muhammad Adnan; Murdan Murdan (JURNAL ISLAM NUSANTARA, 2025)
Polygamous marriage often creates complex relational dynamics that require culturally grounded strategies to maintain harmony. This study analyzes the construction of marital harmony between first and second wives through a comparative socio-legal lens, integrating perspectives from Islamic law and Sasak cultural norms. Using a qualitative approach, data were collected from polygamous families, religious leaders, and customary figures through in-depth interviews and focused observations in selected Sasak communities. Findings show that marital harmony is shaped by three key factors: structured role negotiation between wives, the husband’s equitable fulfillment of nafkah and emotional responsibilities, and the cultural mechanism of silepak, which encourages conflict mediation. Data also reveal that first wives tend to emphasize legal guarantees, whereas second wives rely more on cultural acceptance to maintain relational stability. This study contributes a dual-framework model for analyzing polygamous harmony and recommends strengthening community-based counseling that integrates Islamic legal ethics with local wisdom.